Mathematical Problem-Solving Strategies of Pre-Service Elementary School Teachers in Solving Contextual Problems - Refni Adesia Pradiarti (Jurnal MIPA dan Pembelajarannya, 2026)
This study aims to describe the mathematical problem-solving strategies employed by pre-service elementary school teachers in solving contextual problems based on Polya's problem-solving stages. The study adopted a qualitative approach with a descriptive research design. The participants consisted of 32 students from the Elementary School Teacher Education Program at Sunan Gresik University who completed a mathematical problem-solving test. Three participants were purposively selected to represent high-, moderate-, and low-ability groups. Data were collected through a contextual mathematical problem-solving test, semi-structured interviews, and documentation of the participants' written work. Data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that participants in the high-ability group successfully completed all stages of Polya's problem-solving process systematically, employed appropriate strategies, and accurately interpreted the results within the given context. Participants in the moderate-ability group were able to perform the mathematical procedures correctly but experienced difficulties in reflecting on and interpreting their solutions. Meanwhile, participants in the low-ability group encountered difficulties from the initial stage of understanding the problem, resulting in the use of inappropriate strategies and solutions that did not adequately address the problem requirements. These findings suggest that the ability to understand contextual situations, select appropriate strategies, and reflect on the solution process are key factors distinguishing the mathematical problem-solving performance of pre-service elementary school teachers.